Pengelolaan Desa Wisata Kaba – Kaba, Kecamatan Kediri, Kabupaten Tabanan - I Gusti Ayu Komang Meilinda Wijayanthi; Putri Kusuma Sanjiwani (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
The tourism village is one alternative tourism that is currently growing in the Bali tourism industry, and one of them is the Kaba - Kaba Tourism Village. Kaba Tourism Village - Kaba is a tourism village that has just been established by the Regional Government of Tabanan Regency, so that currently Kaba - Kaba Village is still preparing itself to become a tourist attraction, so this research is important to know how the management that takes place in the Kaba Tourism Village - Kaba so that the village is ready to promote itself as one of the tourist attractions in Tabanan Regency. In this study using primary data sources obtained directly by observation and interviews, and data analysis techniques used in this study are qualitative analysis by reducing the data which is then presented and concluded. The results of this study note that the management of the Kaba - Kaba Tourism Village is fully managed by the Pokdarwis. The manager of the Kaba - Kaba Tourism Village is expected to be able to promote and operate the Kaba - Kaba Tourism Village faster. Keyword: Manajement, Kaba – kaba Tourism Village